Dynamic Full-Duplex Cellular System for Wide Area IoT Network Backbone - Keiichi Mizutani; Kazuki Nishikori; Kyoya Teramae; Hiroto Kuriki; Takeshi Matsumura; Hiroshi Harada (IEEE Open Journal of Vehicular Technology)
This study proposes a dynamic full-duplex cellular (DDC) system by introducing an in-band full-duplex in a phased manner into a conventional time-division duplex (TDD)-based cellular system. Further, we propose and evaluate appropriate user equipment (UE) scheduling and transmission power control schemes for DDC in dense urban multi-cell environments. The proposed DDC sufficiently suppresses inter-cell interference through fully distributed resource allocation, which does not require information exchange among neighboring cells. In particular, the propagation loss compensation factor, UE transmission power limit, and assumed uplink signal-to-noise plus interference power ratio (SINR) adjustment factor prove to be essential. By appropriately setting these factors, the proposed DDC system improves the average throughput of the downlink (DL) by 13.2% and uplink by 31.6% compared with the conventional TDD system. Moreover, we observe a 2.5% improvement in the DL 5% user throughput. The results of this study are expected to contribute to the realization of a high-capacity wide-area IoT network backbone by improving the efficiency of utilization of limited spectral resources, especially in the sub-6 GHz band.